Polypropylene-organoclay nanocomposites containing nucleating agents - Ghugare, S. V.; Govindaiah, P.; Avadhani, C. V. (Polymer Bulletin, 2009)
Polypropylene/organoclay nanocomposites containing nucleating agents, viz., aluminum hydroxybis[2,2-methylenebis(4,6-di-tert-butylphenyl) phosphate (NA21) and 1,3:2,4-bis(3,4-dimethylbenzylidene)sorbitol (Millad 3988), were prepared by direct melt intercalation in a twin-screw extruder. Nucleating agents were added to polypropylene during compounding and their effect on the properties of the nanocomposites was studied. X-ray diffraction (XRD) and transmission electron microscopy (TEM) exhibited clay layers to be intercalated and partially exfoliated. The expansion of inter-gallery distance of the clay layers was governed by the interaction between polypropylene, compatibilizer, and different nucleating agents. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) indicated higher thermal stability and crystallization temperature for nanocomposites compared to virgin polymer. Even a small addition of the nanoscale filler with 0.2% nucleating agents was found to promote concurrently several PP material properties, including improved tensile characteristics, higher Young's modulus, increased thermal stability and rate of crystallization.
Keywords: Nucleating agents; organoclay; Polypropylene nanocomposites; Thermogravimetric analysis; transmission electron microscopy